2006
DOI: 10.1183/09031936.06.00139305
|View full text |Cite
|
Sign up to set email alerts
|

Implications of COPD in patients admitted to the intensive care unit by community-acquired pneumonia

Abstract: The mortality rate of chronic obstructive pulmonary disease (COPD) patients with community-acquired pneumonia (CAP) is reported to be low. However, studies carried out to date have included ,20% of critically ill patients.The current authors performed a secondary analysis of a prospective study evaluating 428 immunocompetent patients admitted to the intensive care unit (ICU) for severe CAP.In total, 176 COPD patients were compared with 252 non-COPD patients. In COPD patients, ICU mortality (odds ratio (OR) 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
113
3
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 28 publications
10
113
3
7
Order By: Relevance
“…COPD was present in a total of 8 patients of which only 4 (3%) were in the survivor group and 5 (31.3%) were in the death group. As in our study, a significantly higher mortality associated with COPD and CAP was reported by Restrepo et al and Rello et al 18,20 The study of Falguera M et al demonstrated association between death from CAP and diabetes mellitus and in the same study diabetes was found to be an independent risk factor for development of pleural effusion. 21 However the results from our study differed in both these respects in that diabetes mellitus was found to have association neither with death (p=0.689), nor with development of effusions.…”
supporting
confidence: 74%
“…COPD was present in a total of 8 patients of which only 4 (3%) were in the survivor group and 5 (31.3%) were in the death group. As in our study, a significantly higher mortality associated with COPD and CAP was reported by Restrepo et al and Rello et al 18,20 The study of Falguera M et al demonstrated association between death from CAP and diabetes mellitus and in the same study diabetes was found to be an independent risk factor for development of pleural effusion. 21 However the results from our study differed in both these respects in that diabetes mellitus was found to have association neither with death (p=0.689), nor with development of effusions.…”
supporting
confidence: 74%
“…23,24 In patients with severe pneumonia, COPD is associated with an unfavorable clinical course, more complications, ICU admission, mechanical ventilation, and higher mortality than in those without COPD. 17,25 We found that hypoalbuminemia was associated with hypoxemia in patients with mild pneumonia. Hypoalbuminemia is also associated with higher pneumonia severity, higher mortality, higher hospital costs, and longer recovery time.…”
Section: Discussionmentioning
confidence: 79%
“…10 Some studies have carefully examined whether patients with community-acquired pneumonia and COPD present differences in clinical manifestations, etiology, or outcome, with special emphasis on mortality compared to those that do not have COPD. 11,12 To our knowledge, the present study is the first to compare the clinical features, etiological distribution, and treatment outcomes of patients with COPD exacerbation versus patients with community-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%